Shui hua mo fa dong wu shi jie Dong wu zhi shi hui ben, shui hua mo fa you xi ka (Xiao guang dian, 2017)
Activity book combined with 5 water-reveal cards, for 3-5 year-old kids to learn about animals in the world. The water-reveal cards can be painted repeatedly.